August Comte's Positivism in Educational Decision Making - Fuad, Rahmad; Hanani, Silfia (Journal of Advanced Islamic Educational Management, 2024)
This research aims to examine the application of Auguste Comte's principles of positivism in decision-making in education management at SDN 02 Aur Kuning. Using descriptive qualitative methods, this study describes the impact of a data-driven approach to education policy. The results show that applying positivism enhances objectivity, accountability and transparency in decision-making and supports continuous improvement in academics and student character building. However, challenges such as limited resources, access to accurate data and integration of religious values with the scientific approach still need to be overcome. This research emphasizes the importance of commitment from all parties to ensure the implementation of positivism can optimally improve the quality of education.